Presupposition, assertion, and definite descriptions - Elbourne, P (Springer, 2021)
In recent work on the semantics of definite descriptions, some theorists (Elbourne in Definite descriptions, Oxford University Press, Oxford, 2013; Schoubye in Noûs 47(3):496–533, 2013) have advocated broadly Fregean accounts, whereby a definite description ‘the F’ introduces a presupposition to the effect that there is exactly one F and refers to it if there is, while other theorists (Abbott, in: Gundel, Hedberg (eds) Reference: Interdisciplinary perspectives, Oxford University Press, Oxford, pp. 61–72, 2008; Hawthorne and Manley in The reference book, Oxford University Press, Oxford, 2012) have advocated accounts whereby ‘the F’ introduces a presupposition to the effect that there is exactly one F but otherwise has the semantics of ‘an F’, introducing existential quantification. It is argued that the latter theories, since they have definite descriptions encode assertoric content to the effect that there is an F, have difficulty accounting for the felicity of ‘The F is G’ when it is already presupposed that there is an F.